2011
DOI: 10.1111/j.1551-2916.2011.05002.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Rutile Nanocrystals Prepared in Aqueous Media at Low Temperature

Abstract: Rutile powder was synthesized via sol–gel processing of Tyzor TE precursor in an aqueous solution at 40°C–50°C. A suite of characterization techniques, including FTIR, Raman, X‐ray, and electron diffraction, were employed to investigate the microstructural evolution. The synthesized powder was phase‐pure rutile possessing high surface area (144.7 m2/g), an average pore size of 24.9 nm, and pore volume of 0.66 cm3/g. A reaction mechanism is proposed for the preferential evolution of rutile over other titania po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…4g shows the selected area electron diffraction (SAED) pattern exhibiting sharp uniform rings, confirming that the beads are highly crystalline and randomly oriented. 22 Analysis of the diffraction pattern undoubtedly indicates that the SMATBs are the anatase polymorph of TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…4g shows the selected area electron diffraction (SAED) pattern exhibiting sharp uniform rings, confirming that the beads are highly crystalline and randomly oriented. 22 Analysis of the diffraction pattern undoubtedly indicates that the SMATBs are the anatase polymorph of TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The aging of titanatrane isopropoxide in HNO 3 (40-50 C, 12-24 h) showed pure rutile. 391 The amorphous titania dissolved into a transparent titania gel in a stirred acidic solution (HCl or HNO 3 ) reprecipitated as rutile aer aging for a long time (48 h) This journal is © The Royal Society of Chemistry 2014 mole fraction of rutile decreased with an increase in the treatment temperature and pure anatase was obtained at temperatures >150 C. It was suggested that a stable rutile nucleus with a compact structure is formed by a very slow reprecipitation rate at temperatures <60 C, while anatase was formed at high temperatures due to a larger reprecipitation rate. 392 In a modied dissolution-reprecipitation process, rutile particles dissolved in H 2 SO 4 and reprecipitated with NH 3 showed anatase-rutile aer calcination (450-900 C, 1 h).…”
Section: Thermolysis With Other Titanium Precursorsmentioning
confidence: 99%
“…430 Compared to the trivial titanium precursor, titanium amino-alcohol complexes exhibit improved hydrolysis-condensation properties over simple alkoxides, allowing for better control in the sol-gel reaction due to its "caged" structure. 391 The titanatrane complex [N(CH 2 CH 2 O) 3 Ti-O i Pr] reacts with water and forms hydroxyl titanium chelate [N(CH 2 CH 2 O) 3 Ti-OH], which is stable in water for an extended period of time. 432a Since the only -OH group is in the complex and no -OH moiety is present in its dimer [N(CH 2 CH 2 O) 3 Ti-O-TiN(CH 2 CH 2 O) 3 ], rutile nucleates without forming anatase.…”
Section: Crystallization From Inorganic Titanium Precursorsmentioning
confidence: 99%
“…The TB-type potassium tantalate K 6 30 reached 93% under UV irradiation for 120 min. The photocatalysis not only destroyed the chromophore of ARG but also decomposed its benzene ring and naphthalene ring partly.…”
Section: Discussionmentioning
confidence: 99%
“…[18,29] Some new bands appeared in the spectrum of the recovered catalyst after the photocatalytic reaction around 2920 cm 1 . The band at 2970-2860 cm 1 represented the CH 2 or CH 3 stretch, [30] which might be due to the formation of intermediates adsorbed on the surface of the catalysts.…”
Section: Photocatalytic Activitymentioning
confidence: 99%